INTERPRETATION OF GEORGE SAUNDERS’ SHORT STORIES (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The importance of understanding George Saunders’ short stories is essential way of revealing the political system of America nowadays. If people are interested in modern reflection of American society they should dig in the Saunders’ world with paying attention to the details that may be interpreted differently.